Efficiency of the peripheral and combined gas-distribution in torches of coppers of the TGM-84 - M. A. Taymarov; R. V. Akhmetova; Yu. V. Lavirko; L. I. Kasimova (Известия высших учебных заведений: Проблемы энергетики)
So far rather large number of torches for chamber combustion of gaseous fuel differing among themselves on the nature of gas-distribution for mixture of fuel with air is known. For domestic oil-gas torches of power coppers their unification as combustion of fuels is characteristic, that is heat of combustion of the burned fuel can change in quite wide limits. Moreover, directly in use on thermal power plant their reconstruction is made for reduction of length of a torch, achievement of uniform radiation of a torch, change of local values of temperatures of a torch or reduction of their maximum values. As a rule, the detailed researches received after reconstruction of these torches are not conducted. Foreign torches are designed and made on combustion of fuel of a concrete type with the set heat of combustion. At the same time the main role for increase in efficiency is assigned to computer regulation of a ratio of fuel and air, gas-distribution - central tubular. Except high cost, the difficulty of application of foreign torches for domestic power coppers is connected with adaptation of automatic equipment of these torches to the system of automation of domestic coppers. Therefore for domestic coppers one of the directions them modernization for the purpose of increase in efficiency is reconstruction of schemes of gas-distribution in the existing torches. In this article the efficiency of application of peripheral tubular gas-distribution in comparison with the combined peripheral tubular gas-distribution combined with conic central gas-distribution when using as the main tagentsialny peripheral twist of air is investigated. These schemes of gas-distribution are applied in coppers of TGM-84A of the Kazan TES-3 and the Nizhnekamsk TES-1 on which experiments on identification of efficiency of these types of gas-distribution for combustion of natural gas of the Urengoy field are made.